2017
DOI: 10.1093/treephys/tpx089
|View full text |Cite
|
Sign up to set email alerts
|

Rapid monoterpene induction promotes the susceptibility of a novel host pine to mountain pine beetle colonization but not to beetle-vectored fungi

Abstract: Chemical induction can drive tree susceptibility to and host range expansions of attacking insects and fungi. Recently, mountain pine beetle (Dendroctonus ponderosae Hopkins; MPB) has expanded its host range from its historic host lodgepole pine (Pinus contorta var. latifolia Douglas ex Loudon) to jack pine (Pinus banksiana Lamb) in western Canada. Beetle success in jack pine forests likely depends upon the suitability of tree chemistry to MPB and its symbiotic phytopathogenic fungi. In particular, how rapid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…The differences in the results of this and the earlier study may be attributed to differences between host tree species in terms of their secondary chemical profiles, how fungi were introduced to trees (artificial inoculation vs. natural beetle colonization), and analytical methods undertaken to quantify the ergosterol concentrations. First, although these two tree species share many secondary compounds, their concentrations show large variation, which may differentially affect fungal growth ( Cale et al, 2017 ; Erbilgin, 2019 ; Wang et al, 2020 ). Second, in the current study, we quantified ergosterol concentration from individual fungal species, while the earlier study quantified ergosterol from trees colonized by MPB without assessing the relative concentrations from each fungus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences in the results of this and the earlier study may be attributed to differences between host tree species in terms of their secondary chemical profiles, how fungi were introduced to trees (artificial inoculation vs. natural beetle colonization), and analytical methods undertaken to quantify the ergosterol concentrations. First, although these two tree species share many secondary compounds, their concentrations show large variation, which may differentially affect fungal growth ( Cale et al, 2017 ; Erbilgin, 2019 ; Wang et al, 2020 ). Second, in the current study, we quantified ergosterol concentration from individual fungal species, while the earlier study quantified ergosterol from trees colonized by MPB without assessing the relative concentrations from each fungus.…”
Section: Discussionmentioning
confidence: 99%
“…Six weeks later, we collected phloem tissue samples from lesions as well as non-infected phloem adjacent to lesions (about 4 cm above the lesions; “non-infected phloem” hereafter; Figure 1 ). During our sampling we observed that fungal inoculations created much longer lesions than mock inoculations, suggesting that our inoculations were successful ( Bonello et al, 2006 ; Cale et al, 2017 , 2019 ). In addition, we confirmed fungal species by subsampling tissues taken from lesions on each tree.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…The defense response is usually induced by the inoculation of trees with an MPB‐associated fungus, and is measured by determining the concentrations of defense chemicals, mainly monoterpenes, in the phloem and necrotic tissues (i.e. lesions caused by infections by beetle symbiotic fungi) (Arango‐Velez et al ., ; Cale et al ., ; Erbilgin et al ., ).…”
Section: Approach Undertakenmentioning
confidence: 97%
“…Similarly, Raffa and Berryman [52] showed that β-myrcene, limonene and terpinolene in combination with αand β-pinene are directly toxic to D. frontalis adults in loblolly pine. The implication of a long-term (65 dpi) induced monoterpenes response can be both beneficial and deleterious to P. strobus; as induction of β-myrcene and β-pinene may promote beetle aggregation [53,54], fostering future beetle attacks. Additionally, as carbohydrate reserves fund monoterpene synthesis [47], prolonged monoterpene production can eventually deplete carbon availability necessary for tree growth.…”
Section: Phenolics and Terpenoids Involved In Eastern White Pine Indumentioning
confidence: 99%